2018
DOI: 10.1002/epi4.12108
|View full text |Cite
|
Sign up to set email alerts
|

Expanding spectrum of RARS2 gene disorders: Myoclonic epilepsy, mental retardation, spasticity, and extrapyramidal features

Abstract: SummaryPontocerebellar hypoplasia type 6 (PCH6) is an autosomal recessive mitochondrial disease, typically characterized by pontine atrophy, vermian hypoplasia, infantile encephalopathy, generalized hypotonia, and intractable seizures. The purpose of this study is to describe the seizures and other neurological manifestations of RARS2 gene mutations and to compare the clinical features with other causes of progressive myoclonic epilepsy. Detailed history, physical examination, and clinical and genetic work‐up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…For Case A, the maternally inherited start-loss variant is at the same position as previously published variants, 15,18,29 and the paternally inherited missense variant is a recurrent pathogenic variant 7,23,25 (Table 1). No other plausible pathogenic variants were identified in the trio genome.…”
Section: Molecular Findingsmentioning
confidence: 83%
See 1 more Smart Citation
“…For Case A, the maternally inherited start-loss variant is at the same position as previously published variants, 15,18,29 and the paternally inherited missense variant is a recurrent pathogenic variant 7,23,25 (Table 1). No other plausible pathogenic variants were identified in the trio genome.…”
Section: Molecular Findingsmentioning
confidence: 83%
“…31/50) (Figure 1B). There are ten recurrent variant positions (p.Met1(Val/Leu) 15,18,29 ; p.Gln12Arg 4,6,13,28 ; c.110+5A>G 1,8,13 ; p.Lys158del 3,7,28 ; p.Gln208* 20,26 ; p.Arg258His 5,26 ; p.Leu283Gln 7,23,25 ; p.Met342Ile 12,20 ; p.Asp515Gly 9,22 ; p.Val522Ile 28,29 ); however no clear genotype-phenotype correlation has been identified. 2 We describe a new RARS2 phenotype of infantile-onset myoclonic developmental and epileptic encephalopathy in two unrelated children and compare this to the epileptology in the previously reported cases.…”
Section: Introductionmentioning
confidence: 99%
“…Mathew et al (20) has reported that two siblings with RARS2 variants started myoclonic jerks after birth, however, related MRI and EEG features during the period of neonate were not provided in their report. Nuclear mitochondrial genes, such as AMT encodes an enzyme system for cleavage of glycine which is confined to the mitochondria and SLC25A22 encodes mitochondrial carriers that transport a variety of metabolites across the inner mitochondrial membrane.…”
Section: Discussionmentioning
confidence: 94%
“…RARS2 (↓1.6X) is the arginyl-tRNA synthetase gene that has been associated with a spectrum of neurological disorders including myoclonic epilepsy, mental retardation, spasticity, and extrapyramidal features [ 48 ]. Patients with RARS2 mutations exhibit early onset hypotonia, epileptic seizures, encephalopathy, and feeding difficulties in a syndrome termed pontocerebellar hypoplasia type 6 (PCH6) [ 49 ].…”
Section: Resultsmentioning
confidence: 99%